Neuroprotective and anti-apoptotic activity of the IL-1 antagonist RAIL-gel in rats after ketamine anesthesia - Belenichev, I. F.; Burlaka, B. S.; Ryzhenko, O. I.; Ryzhenko, V. P.; Aliyeva, O. G.; Makyeyeva, L. V.; Бєленічев, Ігор Федорович; Бурлака, Богдан Сергійович; Риженко, О. І.; Риженко, Віктор Павлович; Алієва, Олена Геннадіївна; Макєєва, Людмила Валеріївна (My University, 2021)
Introduction: The choice of medicines for total intravenous anesthesia remains a relevant issue in practical anesthesiology. Ketamine is a well-known drug that has been widely used in the world, however its’ effect on the CNS is debatable. It is reasonable to question the use of neuroprotective agents to protect against the negative effects of general anesthesia. Some studies have shown the neuroprotective activity of the RAIL. A new dosage form of RAIL - a gel for intranasal administration has been developed. This study was designed to evaluate the neuroprotective and anti-apoptotic activity of RAIL-gel in comparison with Citicoline and Piracetam during ketamine anesthesia Methods: In this study, 50 white nonlinear rats were randomly assigned to 5 groups: intact, ketamine anesthesia group, ketamine anesthesia + Piracetam (500 mg/kg, intraperitoneally) group, ketamine anesthesia + Citicoline (500 mg/kg, intraperitoneally) group, ketamine anesthesia + RAIL-gel (1 mg / kg intranasally) group. Expression of c-fos in the CA1 zone of the hippocampus and concentration of bcl-2 protein in the cytoplasmic fraction of the brain were determined by indirect immunofluorescence and Western blot analysis respectively. Results: Our research demonstrated the neurodegradative effect of ketamine anesthesia. The use of neuroprotective agents (Piracetam, Citicoline, RAIL-gel) in rats after general anesthesia led to a decrease in the neurodegradative effect of ketamine. The neuroprotective effect of RAIL-gel was significantly higher compared to reference drugs (p < 0.05). Conclusion: The neuroprotective effect of RAIL-gel is an experimental justification for further study of IL-1β RAIL antagonist as a potential neuroprotective agent.
I. F. Belenichev - ORCID: 0000-0003-1273-5314, B. S. Burlaka - ORCID: 0000-0003-4539-7331, V. P. Ryzhenko - ORCID: 0000-0003-3466-714, O. G. Aliyeva - ORCID: 0000-0003-1287-674X, L. V. Makyeyeva - ORCID: 0000-0002-3188-2638.
Keywords: IL-1 antagonist; citicoline; piracetam; neuroprotective agents; c bcl-2 proteins; c fos proteins; neurons